IMPLEMENT ONLINE LEARNING USING GOOGLE CLASSROOM APPLICATIONS - Wijaya, Febiyola; Pattipeilohy, Vascolino; Nusi, Ahmad (TELL - US JOURNAL, 2022)
During pandemic learning process mostly occurs online, lecturers cannot supervise students directly just as they were in the classroom. This situation also happened at State Polytechnic of Ambon. In fact, this process is less effective for example students who were late in entering online classes, absent in class due to insufficient phone credits, returning home, and no internet signal. They even claimed to have collected the task, but they actually did not. Moreover, in doing the individual tasks, 2-3 students who work together which results on the same exam answers or “copy-paste” system. This study examines the stages of online learning using Google Classroom to achieve effective learning. The method of this research is descriptive research. The result shows the method of implementing Google Classroom uses several stages, namely: 1). Introduction stage: looking for various sources that explain about Google Classroom applications and introducing to students, 2). Implementation Stage: involving students in using Google Classroom applications in the online learning process,  3). Evaluation stage, results achieved during use of Google Classroom application. Besides presenting the stages of online learning using Google Classroom application, this study also examined its impacts on student discipline and honesty.  The data shows that Google Classroom influenced 31.4% on discipline aspects and only 3, 7% on honesty.